PENGARUH PENAMBAHAN ION Fe3+ TERHADAP AKTIVITAS XILANASE DARI Trichoderma viride - Sulistyaningtyas, Ardyan Sukma; Prasetyawan, Sasangka; Sutrisno, Sutrisno (Jurusan Kimia, FMIPA Universitas Brawijaya, 2013)
Xylanase is an enzyme that catalyzes the hydrolysis reaction substrate xylan (hemicellulose) into xylose. This study was conducted to determine the effect of Fe3+ on the activity of xylanase from Trichoderma viride using corn strove as an inducers. Effect of the addition of Fe3+ ions on xylanase activity was determined by comparing the xylanase activity with the addition of Fe3+ ions and xylanase activity without the addition of Fe3+ ions. Xylanase activity was determined by measuring the reducing sugar xylose spectrophotometrically using 3,5-dinitrosalisilat acid reagent (DNS). The results showed that the addition of Fe3+ ions in the concentration range of 5-35 mM can increase the activity of xylanase Keywords: Xylanase, Fe3+, Trichoderma viride, Corn Strove